The Effect of Controversy on Brand Visibility and Consumer Awareness in Formula One - Lees, Samuel Robert (2008)
There has been a degree of research conducted into the effect that controversy has on brand equity and consumer knowledge. This study aims to extend this knowledge by addressing whether the existence of indirect controversy on different types of consumers can benefit a sponsor by increasing visibility. Can a consumer become aware of a sponsor's activities merely as a result of controversy i.e. without a prior awareness of the operating environment? Are low-commitment consumers less inclined to attribute negative information to sponsors than those with a high-commitment? Does a negative perception of the environment lead to an automatic connection between a sponsor and controversy regardless of the weakness of the relationship?